1994
DOI: 10.1099/13500872-140-8-1989
|View full text |Cite
|
Sign up to set email alerts
|

A family of diacyltrehaloses isolated from Mycobacterium fortuitum

Abstract: A trehalose-containing glycolipid was detected in several strains of Mycobacteriutn fortuitum and characterized as 2,3-di-O-acyltrehaIose (DAT) by constituents of the molecule were identified as a mixture of straight-chain (14-18 carbon atoms) and methyl-branched-chain (17-21 carbon atoms) fatty acyl groups. DAT was further fractionated by reverse phase TLC into four fractions that were designated DAT-I-DAT-IV. DAT-I contained 70-75 O/ O straightchain acyl substituents (hexadecanoyl and octadecanoyl predominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…The eluates (each 200-300 ml) were monitored for various types of lipids on TLC silica gel 60 F #&% plates (Merck) using chloroform\methanol\water (65 : 25 : 4, by vol.). The positions of the separated compounds were detected by spraying with a 5 % (w\v) ethanolic solution of molybdophosphoric acid, followed by heating for 10 min at 180 mC (visualization of all lipid-containing compounds) (Ariza et al, 1994). To detect sugar-containing lipids, the plates were sprayed with orcinol (0n5%, w\v, in 3 % H # SO % in methanol) followed by heating.…”
Section: Lipid Analysismentioning
confidence: 99%
“…The eluates (each 200-300 ml) were monitored for various types of lipids on TLC silica gel 60 F #&% plates (Merck) using chloroform\methanol\water (65 : 25 : 4, by vol.). The positions of the separated compounds were detected by spraying with a 5 % (w\v) ethanolic solution of molybdophosphoric acid, followed by heating for 10 min at 180 mC (visualization of all lipid-containing compounds) (Ariza et al, 1994). To detect sugar-containing lipids, the plates were sprayed with orcinol (0n5%, w\v, in 3 % H # SO % in methanol) followed by heating.…”
Section: Lipid Analysismentioning
confidence: 99%
“…chelonae and M. absccssus) and of a group of strains, the third biovariant complex of M. fortuitum, which is unique in its immunodiffusion pattern and acid production from various carbohydrates (LCvy-Frebault et al, 1983;Pattyn et al, 1974;Silcox et al, 1981). Chemical analyses of the representative strains of the lour species demonstrated the occurrence of species-specific alkali-labile glycolipid in M. fortuitum (Ariza et al, 1994;Gautier et al, 1992;Hamid et al, 1993;Tsang et al, 1984;Sempere et al, 1993) and alkalistable glycolipids in the three other species (L6pez Marin et al, 1991(L6pez Marin et al, , 1992(L6pez Marin et al, , 1994Tsang et al, 1984). The present study was performed to characterize specific glycolipids in six strains that belong to the third biovariant complex of M. fortuitum (mannitol-positive and inositol-positive) and showed that this group of organisms is heterogeneous, in agreement with the data obtained by others by means of genotypic (Kirschner et al, 1992;Springer et al, 1995) and biochemical approaches (Wallace et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Replacement of an acetyl group by a fatty acyl substituent may explain the difference in the mobilities of the two glycolipids, as almost identical fatty acyl residues were identified in both studies. Nevertheless, the presence o f a tetraacylated triglucoside may typify some strains of the third biovariant complex, since biochemically well-characterized strains of M. fortuitum, including the type strain, were shown to synthesize alkali-labile glycolipids that consisted of 2,3-acy12trehalose, 2,3,4-acy13trehalose and 2,3,6-acy13trehalose (Ariza et al, 1994;Gautier et al, 1992;Hamid et al, 1993;Sempere et al, 1993). These acyltrehaloses differ from the major alkali-labile glycolipid of the third biovariant complex both in the structure of the carbohydrate moiety and in the location of the acyl substitutents, which suggests that the latter compound is not biosynthetically derived from the former substances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The resulting monomethyl branched shortchain acids were found in SLs, PATs, and the more polar DATs. Such unsaturated monomethyl branched acids have been reported in the various glycolipids of Mycobacterium fortuitum (1,16,26,30), but their presence in M. tuberculosis has not been previously noted. The use of [1-14 C]propionic acid and careful separation of the methyl esters by argentation chromatography allowed us to detect these minor components.…”
mentioning
confidence: 99%